Development of collaborative TPACK module for continuing professional development in a higher education institution / Vinothini Vasodavan - Vinothini , Vasodavan (2020)
Teaching and learning in higher education should be more than just a transmission of knowledge. The focus should be on acquiring skills for interacting, applying, evaluating and creating new knowledge as well as problem solving. This can be achieved through social interactions and cognitive process during collaborative learning (CL) using collaborative learning (CL) tools. Therefore, instructors should be able to integrate CL tools effectively into instruction by having a good understanding of incorporating them into appropriate pedagogy and content. Hence, in this study a Collaborative TPACK module was developed for continuing professional development (CPD) to build instructor’s skills and knowledge in TPACK so that they able to teach meaningfully with CL tools. A design and developmental research with three phases; need analysis; design and development; implementation and evaluation were employed. In the first phase, seven instructors, two Head of Training Units and a trainer were interviewed to gain insights on instructors’ current technology skills and perspective regarding the use of CL and CL tools. In addition, data was triangulated with previous TPACK training evaluation and learning activities took place in the university learning management system (LMS) to identify the frequently used tools by instructors for teaching. Instructors seems to have a basic knowledge pertaining to the usage of technology in education but lack of knowledge on CL concepts and implementation in the teaching process. Hence, there was a need for module development. In the design phase, the elements appropriate for the Collaborative TPACK module was determined using the Fuzzy Delphi Method (FDM). First, a semi structured interview was conducted with four experts and the data was analysed thematically to design the FDM survey. The survey was administered to sixteen experts for consensus on the elements in the module. Consensus was achieved for the elements of learning outcome, content, instructional strategies, resources/media, assessment and delivery that should be incorporated into the module. After the module development, the Collaborative TPACK module was reviewed by four experts before implementation. The module was implemented among thirty-four instructors in one of the public higher education institutions in Klang Valley using one group experimental design. In addition, seven instructors participated in the follow up session by completing several tasks such as lesson design, lesson observation and designing the e-portfolio. In addition, post lesson observation was conducted to gather rich description about their experiences and opinion teaching with collaborative TPACK. Besides that, a survey was administered to explore the instructors’ perception on the module usability. Instructors found that the module is usable form the pedagogical and technical aspect. The Wilcoxon Matched-pairs Signed Ranks Test indicates a significant difference in the pre and post TPACK score and t-test analysis indicates a significant difference in the pre, and post-test score due to the implementation of the Collaborative TPACK module. This study contributed to the element of collaboration in the existing TPACK model which known as Collaborative TPACK by incorporating Merrill's First Principles and taxonomy of learning outcome in a CPD programme. This study also adds to the repertoire of knowledge the important of continues assessment with inclusion of phase five, transfer of knowledge and the retention of expertise. It is recommended that the module should be implemented in other higher education institutions to develop instructors’ skills and knowledge in collaborative TPACK